PRESENTATION PRACTICE PRODUCTION VS TASK-BASED LANGUAGE TEACHING: A COMPARISON OF TWO TEACHING TEMPLATES - Pratista, Ganang Yudha (Universitas Muhammadiyah Ponorogo, 2023)
A number of statements are addressed to defend and criticize two popular teaching templates: Presentation Practice Production (PPP) and Task-Based Language Teaching (TBLT). Advocates of each teaching template claim that their method is more effectively to be implemented in English language teaching than the other. This article compares these teaching templates to find out their strengths and weaknesses. This paper is a library study. It employs theoretical analysis to examine experts, prominent figures, and previous important theories and findings on discussing the same topic. The idea of PPP is a deductive and teacher-centered approach with focuses mainly on accuracy by means of drilling practice. Meanwhile, TBLT encourages students to be communicative in the classroom through language input and pushes the teacher to be a facilitator. The result of the comparison indicates that using PPP is effective in preparing students to take exams or tests, while TBLT is useful to accommodate students’ real-life communicative purposes. As these teaching templates are effective in certain contexts, teachers should consider the learning goals before deciding to implement either PPP or TBLT.